Treatment of spentwash using chemically modified bagasse and colour removal studies - Mane, Jyoti D.; Modi, Shewta; Nagawade, Swati; Phadnis, S. P.; Bhandari, Vinay M. (Bioresource Technology, 2006)
Studies were carried out on derivatisation of bagasse into an ion exchange material and application of this chemically modified bagasse in the treatment of distillery wastewater. It was found that CHPTAC bagasse with HCl treatment and DEAE-bagasse in its free base form were most effective in colour removal and the mechanism of colour removal indicated significant contribution of both, the conventional ion exchange and the chemical sorption. (c) 2005 Elsevier Ltd. All rights
Keywords: decolourisation; distillery effluent; modified biomass; vinasse